2019
DOI: 10.1111/twec.12879
|View full text |Cite
|
Sign up to set email alerts
|

The role of FDI in structural change: Evidence from Mexico

Abstract: Foreign direct investment (FDI) flows to Mexico are substantial and play an important role in the Mexican economy since the mid‐1990s. These investments reflect the activities of multinational firms that shape to some extent the economic landscape and sectoral structure in this host country. We illustrate that there is considerable variation in the amounts of FDI and structural change within the country and across time. Based on this, the paper's main purpose is to analyse whether there is a significant impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 28 publications
0
11
0
6
Order By: Relevance
“…A large number of studies found that the presence of MNCs contributed to TFP growth via spillovers from both horizontal and vertical linkages with MNCs (Ramirez 2006;Suyanto, Salim and Bloch;Fernandes and Paunov, 2012;Anwar and Nguyen, 2014) across various levels of aggregation (Liu and Wang, 2003;Peluffo, 2015;Herzer, 2013Herzer, , 2017Mühlen and Escobar, 2019;). These impacts manifested by raising the industrial competitiveness of manufacturing, by contributing to labour-movement into productive manufacturing and services or simply due to the higher productivity of foreign firms (Fan and Hu, 2007;Lin, Lee and Yang, 2011;Fan, Hu and Kwan, 2019).…”
Section: Productivity Export Competitiveness and Export Growth (C-d)mentioning
confidence: 99%
See 2 more Smart Citations
“…A large number of studies found that the presence of MNCs contributed to TFP growth via spillovers from both horizontal and vertical linkages with MNCs (Ramirez 2006;Suyanto, Salim and Bloch;Fernandes and Paunov, 2012;Anwar and Nguyen, 2014) across various levels of aggregation (Liu and Wang, 2003;Peluffo, 2015;Herzer, 2013Herzer, , 2017Mühlen and Escobar, 2019;). These impacts manifested by raising the industrial competitiveness of manufacturing, by contributing to labour-movement into productive manufacturing and services or simply due to the higher productivity of foreign firms (Fan and Hu, 2007;Lin, Lee and Yang, 2011;Fan, Hu and Kwan, 2019).…”
Section: Productivity Export Competitiveness and Export Growth (C-d)mentioning
confidence: 99%
“…While the growth benefits of FDI have been studied extensively, its impact on structural transformation has largely been ignored in the literature (Mühlen and Escobar, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sur le plan empirique, étudiant les effets des IDE sur la transformation structurelle au Mexique, Mühlen et Escobar (2020) ont introduit les migrations nationales nettes et les migrations internationales nettes dans un modèle pour contrôler les potentiels effets des mouvements nationaux et internationaux des travailleurs sur la réallocation de la main-d ' oeuvre. Les auteurs ont montré que les migrations nationales nettes contribuent négativement à la réallocation de la main-d ' oeuvre peu qualifiée entre les secteurs d ' activités au Mexique.…”
Section: Revue Empirique De L ' Effet De L ' éMigration Sur La Transf...unclassified
“…There are a large number of literatures on international technology spillovers, and the perspectives and indicators are quite different. Some studies found that the effect of FDI technology spillover was not always significant, and the impacts are contingent on regional conditions, yet some found that FDI did not improve the local innovation ability, but had an inhibiting effect [9][10][11][12][13][14][15][16]. The other important issue is the relationship between IPR protection and RTI, which is how IPR protection influence RTI.…”
Section: Introductionmentioning
confidence: 99%